Genotype × environment interaction analysis of polyphenol content and antioxidant activity of exotic Arachis hypogaea varieties in the Sudano-Sahelian zone of Cameroon. - Dounia Désiré; Nassourou Maina Antoine; Dolinassou Souina; Noubissié Tchiagam Jean-Baptiste (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
The objective of this study is to analyze the effects of genotype × environment interaction on seeds polyphenol content and antioxidant activity of exotic groundnut (Arachis hypogaea) varieties grown in the Sudano-Sahelian zone of Cameroon. The field study was conducted in the localities of Gazawa, Bocklé and Dang during 2019 growing season using a randomized complete block design with three replications. Combined analysis of variance was performed using GEST 98 software. The analysis of variance showed significant difference (p<0.05) within the fifteen genotypes for total phenol content and antioxidant activity. The highest total polyphenol contents were noted for 58-619 (1.72 EAG/100g) and R4-A (1.64 EAG/100g) lines while varieties 58-619, EC21164 and R4-A showed largest antioxidant activity (79.96; 76.97 and 76.18 mg TE/g DM). Combined analysis of variance attested that polyphenol content and antioxidant activity were influenced only by genotype effects accounting respectively for 91.96% and 96.05% of the total variation of both traits. The effects of genotype × environment interaction (7.14 and 3.82% of the total sum of square) and environmental effects (0.86 and 0.13%) were not significant in our study area. For these traits, varietal improvement should be given due considerations.